The operation work evaluation and maintenance of Medan Krio Irrigation system in Sunggal District Deli Serdang regency - Muhammad Satria Sebayang; Sumono Sumono; Achwil Putra Munir (Universitas Sumatera Utara, 2014)
Medan Krio irrigation area is an irrigation area which has 2800 Ha width. This irrigation area can be classified as technical irrigation network. This research was conducted to evaluate the operation performance and maintenance the Medan Krio irrigation system. Some indicators which were used to know the work of the irrigation system were : functional work and irrigation network infrastructure, water sufficiency level, water distribution compatibility level, government institutional management, human resource and farmer institutional work. In this research, it was obtained that functional work and irrigation network infrastructure were very bad, water sufficiency level was less,water distribution compatibility level was good, government institutional management was very good, human resource was enough and farmer institutional work was very bad but in over all work evaluation and maintenance of Medan Krio irrigation system were still can be categorized as good. Keyword : Operation and maintenance, Medan Krio irrigation system.